Epidemiological analysis of self-harm and suicide attempts in Iran: a cross-sectional study in Kurdistan’s emergency hospitals - Armin Saedi; Bakhtiar Piroozi; Ghobad Moradi; Media Babahajiani; Kourosh akhbari; Leila Azizkhani (International Journal of Emergency Medicine)
Abstract Background Self-harm and suicide are major global public health issues, especially in low- and middle-income nations. Finding trends and risk factors is essential to creating successful solutions. The purpose of this study was to look into the risk factors and epidemiological characteristics of self-harm and suicide attempts among patients who were hospitalized to the emergency rooms at Kurdistan hospitals in 2021–2022. Methods A cross-sectional study was conducted on 604 cases of self-harm and suicide attempts. Data were extracted from medical records, including demographic, clinical, and social variables. Statistical analysis was performed using SPSS (version 24), employing chi-square tests to determine associations between variables and outcomes. Results The majority of patients (48.8%) were male, and the most affected age group was 17–40 years. Recovery or fatality outcomes were significantly associated with gender (p < 0.05), age group (p < 0.01), and method of self-harm (p < 0.001). Drug overdose (71%) was the most common method, with a recovery rate of 88% (p < 0.01), while hanging had the highest fatality rate at 40% (p < 0.001). Among the cases, 83.6% were discharged after treatment, while 16.4% resulted in death due to suicide attempts. Conclusion The study identifies important clinical and demographic trends linked to suicide attempts and self-harm. Young adults, people with long-term medical or mental health issues, and those who are struggling financially should all be the focus of preventive programs. To lower the suicide rate, public health initiatives must give mental health services and community awareness campaigns first priority.